Influencing factors of LDCT recommendation by physicians in Sichuan Province, China - Li, Ruicen; Chai, Qi; Chen, Feng; Liu, Qing; Zhang, Hong (Frontiers in Oncology, 2023)
Abstract: The study aimed to investigate the influencing factors of physicians in recommending low-dose computed tomography (LDCT) for lung cancer screening to high-risk groups. A total of 1767 participants with good knowledge of LDCT were included in a cross-sectional study. Data about physicians’ demographics, perception of barriers on LDCT screening, medical conditions for practicing medicine and the behavior of recommending LDCT were collected by a questionnaire. Physicians who care about the transportation convenience of patients were less likely to recommend LDCT (OR 0.568, 95% CI (0.423 to 0.763), p < 0.05). The physicians who considered LDCT expensive, recommended LDCT less than others (OR 0.308, 95% CI (0.186 to 0.510), p < 0.05). The false positive rate of LDCT can decrease the possibility of physicians’ recommending (OR 0.542, 95% CI (0.387 to 0.758), p < 0.05). The physicians in oncology department and health management center were more likely to recommend LDCT (OR 2.282, 95% CI (1.557 to 3.345); OR 2.476, 95% CI (1.618 to 3.791)). The convenience of transportation, the price, and the false positive rate may be the main concerns among physicians on recommending LDCT to high-risk groups. The influencing factors of physicians’ recommending on LDCT was various. Information technology, government support in price and self-improvement of LDCT should be gathered together to break the barriers on physicians’ recommending on LDCT.